Item Analysis of Multiple Choice Questions of Anatomy at Aziz Fatimah Medical and Dental College, Faisalabad - Quddus Ur Rehman, Farhat Humayun, M Adeel Alam Shah, Sajjad Ghani, Kamran Afzal, Rifat Humayun (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of our study was to evaluate MCQs in send up exam of 2nd year MBBS. To discard or change poor items with low discriminatory index, very easy and very difficult items and items with more than one non functional distracters. Study design: The cross-sectional study. Place: Department of Anatomy, Aziz Fatimah Medical and Dental College. Faisalabad. Duration of study: One month (December 2021) Methodology: Total 45 MCQs for the subject of Anatomy were constructed for 100 students of 2nd year MBBS send up Examination 2021. The MCQs consisted of one statement with four distractor & one correct option. Data of MCQs attempted by the students was analyzed by using Microsoft Excel 2010. The difficulty index, discrimination index and distractor efficiency were the parameters used for analysis. Results: Total 180 distractors were evaluated. The average number for difficulty index was 55.57 while that for discrimination index was 0.44. Out of 180 distractors, 41 nonfunctional distractors were seen in 26 items. Conclusion: Most MCQs fall within an average to easy difficulty index level i.e. 30 out of 45 MCQs. Most MCQs fulfill the criteria of very good discrimination index i.e. 27 out of 45. Most MCQs have either nil, or one or two non-functional distractors. i.e. 43 out of 45.